Solution
Once we have this first solution we will then assume that a second solution will have the form
y2(x) = v(x)y1(x) or y2(x) = v(x)x10
Differentiating
y2‘(x) = v’(x)x10 + 10v(x)x9 , y2‘’(x) = v’’(x)x10 + 20v’(x)x9 + 90v(x)x8
Plugging these into the differential equation gives
v’’(x)x12 + 20v’(x)x11 + 90v(x)x10 - 7v’(x)x11 - 70v(x)x10 - 20v(x)x10 = 0
v’’(x)x + 13v’(x) = 0
Change of variable w(x) = v’(x), v’’(x) = w’(x) => xw’ + 13 w = 0 => w(x) = Cx-13 => v(x) = -Cx-12/12+ D
Therefore for C = -12 , D = 0 we obtain y2(x) = v(x)x10 = x-2
Then general solution will then be
y(x) = Ax10 + Bx-2
Comments
Leave a comment